An in vivo comparative study of the gelatin microtissue‐based bottom‐up strategy and top‐down strategy in bone tissue engineering application. Issue 3 (5th December 2018) - Luo, Chao; Fang, Huimin; Li, Jialun; Hou, Jinfei; Yang, Jie; Yuan, Quan; Guo, Liang; Zhong, Aimei; Wang, Jiecong; Sun, Jiaming; Wang, Zhenxing
Abstract: Tissue‐engineered bone grafts (TEBGs) represent a promising treatment for bone defects. Nevertheless, drawbacks of the current construction strategy (top‐down [TD] strategy) such as limited transmission of nutrients and nonuniform distribution of seeded cells, result in an unsatisfied therapeutic effect on large segmental bone defects. Theoretically, tissue‐engineered microtissue (TEMT)‐based bottom‐up (BU) strategy is effective in preserving seed cells and vascularization, thus being regarded as a better alternative for TEBGs. Yet, there are few studies focusing on the comparison of the in vivo performance of TEBGs fabricated by TD or BU strategy. Here, we developed an ectopic bone formation rat model to compare the performance of these two construction strategies in vivo. TEBGs made from gelatin TEMT (BU strategy) and bulk tissue (BT; TD strategy) were seeded with equal number of rat bone marrow‐derived mesenchymal stem cells and fabricated in 5 mm polydimethylsiloxane chambers. The grafts were implanted into subcutaneous pockets in the same rat. Four weeks after implantation, microcomputed tomography and hematoxylin and eosin staining results demonstrated that more bony tissue was formed in the microtissue (MT) group than in the BT group. CD31 staining further confirmed that there were more blood vessels in the MT group, indicating that the BU strategy was superior in inducing angiogenesis. This comparative study provides evidence that the BU construction strategy is more effective for in vivo application and bone defect treatment by bone tissue engineering. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 107A: 678–688, 2019.